Kierkegaard's Journals and Notebooks Volume 11: Part 1, Loose Papers, 1830-1843 - Kierkegaard, Søren (Kierkegaard's Journals and Notebooks, 2019)
For over a century, the Danish thinker Søren Kierkegaard (1813–55) has been at the center of a number of important discussions, concerning not only philosophy and theology but also, more recently, fields such as social thought, psychology, and contemporary aesthetics, especially literary theory.Despite his relatively short life, Kierkegaard was an extraordinarily prolific writer, as attested to by the 26-volume Princeton University Press edition of all of his published writings. But Kierkegaard left behind nearly as much unpublished writing, most of which consists of what are called his "journals and notebooks." Kierkegaard has long been recognized as one of history’s great journal keepers, but only rather small portions of his journals and notebooks are what we usually understand by the term "diaries." By far the greater part of Kierkegaard’s journals and notebooks consists of reflections on a myriad of subjects—philosophical, religious, political, personal.